2002
DOI: 10.1159/000065172
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of Arthropod Cross-Reactivity: IgE-Binding Cross-Reactive Epitopes of Shrimp, House Dust Mite and Cockroach Tropomyosins

Abstract: Background: Shrimp may cross-react with other crustaceans and mollusks and nonedible arthropods such as insects (cockroach and chironomids), arachnids (house dust mites) and even nematodes. Since the muscle protein tropomyosin has been implicated as a possible cross-reacting allergen, this study characterized the IgE-binding epitopes in shrimp tropomyosin, Pen a 1, that cross-react with other allergenic invertebrate tropomyosins in house dust mites (Der p 10, Der f 10) and cockroaches (Per a 7). Pen a 1-reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
203
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(217 citation statements)
references
References 24 publications
11
203
1
2
Order By: Relevance
“…Nationally representative data from NHANES 2005-2006 demonstrate similar associations to NCICAS between high shrimp sensitization in non-hispanic blacks of lower socioeconomic status (Table 3). It is well-known that cockroach, dust mite and shrimp tropomyosins share high sequence identity (~80%) [8] and with the additional exposure data that was collected in thi s population, we not only found a high correlation between both cockroach IgE and shrimp IgE, but a high correlation between exposure to cockroach and shrimp IgE as well. In contrast, we did not find a correlation between dust mite exposure and shrimp IgE.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Nationally representative data from NHANES 2005-2006 demonstrate similar associations to NCICAS between high shrimp sensitization in non-hispanic blacks of lower socioeconomic status (Table 3). It is well-known that cockroach, dust mite and shrimp tropomyosins share high sequence identity (~80%) [8] and with the additional exposure data that was collected in thi s population, we not only found a high correlation between both cockroach IgE and shrimp IgE, but a high correlation between exposure to cockroach and shrimp IgE as well. In contrast, we did not find a correlation between dust mite exposure and shrimp IgE.…”
Section: Discussionsupporting
confidence: 62%
“…However, it is well known that IgE-binding cross-reactive epitopes between food allergens and environmental allergens may contribute to elevated IgE levels [6][7][8]. In particular, house dust mite and cockroach tropomyosins can account for the presence of detectable IgE to shrimp, even in unexposed individuals [9].…”
Section: Introductionmentioning
confidence: 99%
“…IgE epitopes of Cyp c 1, a prominent class I food allergen, capable of inducing severe systemic anaphylactic reactions, thus seem to be of the conformational type. In case of other class I food allergens, which frequently elicit life-threatening anaphylactic reactions, such as the major peanut allergens Ara h 1, Ara h 2, and Ara h 3 (32-34), the major shrimp allergen, Pen a 1 (35), and major milk allergens (36,37), it has been reported that IgE-binding primarily occurs to linear epitopes (reviewed in Ref. 12).…”
Section: Discussionmentioning
confidence: 99%
“…Esta reacción cruzada puede desencadenar una respuesta alérgica en personas con alergia a los ácaros, cuando estos consumen alimentos como el camarón o el caracol (74). Existe alrededor de 81 % de identidad en las secuencias de aminoácidos entre las tropomiosinas del ácaro D. pteronyssinus (Der p 10), la de la cucaracha B. germanica (Bla g 7) y la del camarón P. monodon (Pen m 1) (76). En este importante grado de homología estructural y la presencia epítopos antigénicos compartidos, reside parte de las bases inmunológicas de la reacción cruzada entre estas diversas fuentes de alérgenos.…”
Section: Reacción Alérgica Cruzada Entre El Camarón Y Otras Fuentes Dunclassified